Does the Indian Financial Market Nosedive because of the COVID-19 Outbreak, in Comparison to after Demonetisation and the GST?. Issue 10 (8th August 2020) - Mishra, Alok Kumar; Rath, Badri Narayan; Dash, Aruna Kumar
ABSTRACT: We investigate the impact of COVID-19 on the Indian financial market and compare it with the outcomes of two recent structural changes of the Indian economy: demonetization and implementation of the Goods and Services Tax (GST). Using daily stock return, net foreign institutional investment, and exchange rate data from January 3, 2003 to April 20, 2020, we find negative stock returns for all the indices during the COVID-19 outbreak, unlike during the post-demonetization and GST phases. Markov switching vector autoregression shows the impact of COVID-19 on stock returns is severe in comparison to that of demonetization and the GST.